Familial polyposis: Subtotal proctocolectomy with descent of the ascending colon to the anal canal - Palma, Eduardo; Oronoz, Luis (Cirugía del Uruguay, 1979)
A patient suffering from diffuse polyposis accompanied by cancerous rectal degeneration was treated by surgery consisting of sub - total procto - colectomy, with preservation of cecum and proxmal half qf ascending colon anatomosed to anal canal. Follow-up of patient has been clinical, endoscopic and radiological for 16 years and she is considered cured oncologically. Rotation and descent of cecum and proximal ascenling colon have funcioned perfectly. The colon, anatomically reduced by 85 % , has adapted itself and functions perfectly with only 15 o of its length, forming solid or doughy stools, with normal characteristics. Anal canal has functioned normally with one of two daily dejections and total continency with respect to solid and liquid faces.